2018
DOI: 10.1016/j.radi.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Embedding consultant radiographer roles within radiology departments: A framework for success

Abstract: Objectives: Many organisations struggle to clearly differentiate the radiographer consultant role from advanced or specialist practice, with newly appointed consultant practitioners often illprepared for working at this level. This article discusses the design, implementation and validation of an outcomes framework for benchmarking competencies for trainee or new-in-post consultant radiographers. Methods: Five experienced radiographers from different clinical specialisms were seconded to a twelve month consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Within nursing, where ACP roles have been implemented for many years, international studies continue to reveal variation in requirements for ACPs and a lack of role clarity. [9][10][11][12] Previous studies have also highlighted the plethora of titles in use in AHP ACP roles 8,13,14 and for nursing ACP roles too. 15,16 HEE 3 acknowledged the range of titles used and the confusion caused, but further raised that some posts with "advanced" in the title may not actually meet the criteria for ACP roles, thus highlighting a further issue to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Within nursing, where ACP roles have been implemented for many years, international studies continue to reveal variation in requirements for ACPs and a lack of role clarity. [9][10][11][12] Previous studies have also highlighted the plethora of titles in use in AHP ACP roles 8,13,14 and for nursing ACP roles too. 15,16 HEE 3 acknowledged the range of titles used and the confusion caused, but further raised that some posts with "advanced" in the title may not actually meet the criteria for ACP roles, thus highlighting a further issue to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a defined role, stakeholder engagement and acceptance were the key features to address for successful implementation, however, they further identified that the complexity of different work and social contexts imply that addressing these concepts may require a varied approach [54] . A ten-year longitudinal study of a consultant radiographer framework has also highlighted the flexibility required for successful implementation of an advanced role [55] .…”
Section: Discussionmentioning
confidence: 99%
“…Working at a clinical, organisational, system and national level requires a range of leadership styles (Chapman et al 2014;Booth et al 2017) and a development programme. Within the study organisation the peer support and credibility of the role (and individuals) has been built over time and this has likely influenced the reach of the roles internally and externally (Nightingale et al 2018). Similar findings have been found in the work exploring nurse and AHP roles led by Rosser (Rosser et al 2017a(Rosser et al , 2017b.…”
Section: Discussionmentioning
confidence: 99%